Effect of structural design on lnGaN based green LEOs with AIGaN cap layer - Taib, M. l. Md; Alhassan, A. I.; Muhammed, M. M.; Ajia, I. A.; Zainal, N. (2017)
The efficiency of the green light emitting diodes (LEOs) is reported to degrade significantly due to high dislocations density and quantum-confinement Stark effect (OCSE), which results in droop efficiency at higher current. To address this issue, this work proposes the introduction of lnGaN layer before the multi-quantum wells (MOWs), and lnGaN barrier layer in the MOWs structure. This reduces the dislocations density and OCSE, which then improves the efficiency of the device. Three different structures of green LEOs with AIGaN cap layer have been grown on patterned sapphire substrate (PSS) using MOCVO system, which are 1) standard sample, 2) sample with lnGaN barrier and 3) sample with UIO lnGaN layer. Both symmetric (002) and asymmetric (102) XRO rocking curve scans of sample with UIO lnGaN layer showed the lowest full-width-half-maximum (FWHM) value of 229 arcsec and 258 arcsec, respectively, as compared to its counterparts. This reveals that the introduction of UIO lnGaN layer helped in the reduction of dislocations density. Furthermore, AFM results revealed that the lowest surface roughness of 4.56 nm is obtained when UIO lnGaN layer is introduced. Such results are correlated with the XRO rocking curve results, suggesting the reduction of the defective areas on the surface. A temperature-dependent photoluminescence (TOPL) measurement was performed to obtain the emission wavelength behavior and integrated intensity of the peak energy. A higher MOW internal quantum efficiency (IOE) of 34.36% was obtained in sample with UIO lnGaN layer than that of 8.13% and 18.17%, for standard sample and sample with lnGaN barrier, respectively. Overall, the introduction of UIO lnGaN layer in the green LEOs structure helped to improve the structural, surface and optical properties of the device.